PROCESS OF FILLING THE LEXICAL GAPS IN THE UZBEK LANGUAGE (EXAMPLE OF THE LAST HUNDRED YEARS) - Khasanov, Abdumannon (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2023)
The article analyzes the issues of enriching the vocabulary of the Uzbek language over the past hundred years. Observing the development of the vocabulary of a language in a certain period, one can determine the gradual development of the vocabulary of the language, the emergence of new words that name the concepts which do not yet have their representatives. Such observations make it possible to assess the relation of the vocabulary of the language to social life, the development of thinking in proportion to its development, the effective methods in enriching it at the expense of internal resources. This article has focused on the enrichment, standardization and streamlining of language vocabulary since the second quarter of the XX century. In particular, proposals and recommendations for including important words that are rarely used in lexicographic and dialectological studies into the lexicon of the literary language, as well as the norms and principles that should be followed in this case, were also discussed. It is emphasized that the attention to the internal possibilities in enriching the vocabulary of the language has linguistic and -social significance.